2000
DOI: 10.1071/pp00011
|View full text |Cite
|
Sign up to set email alerts
|

The herbicidally active compound N-2-(5-chloro-pyridyl) aminomethylene bisphosphonic acid acts by inhibiting both glutamine and aromatic amino acid biosynthesis

Abstract: Abstract. The effect of the herbicidally active compound N-2-(5-chloro-pyridyl)aminomethylene bisphosphonic acid (Cl-pyr-AMBPA), previously found in vitro to inhibit the activity of the first enzyme in the shikimate pathway 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase, was investigated in vivo on suspension cultured cells of Nicotiana plumbaginifolia Viviani. Amino acid pool measurement showed an actual reduction of tyrosine, tryptophan and phenylalanine level following the addition of the compound to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
(28 reference statements)
2
16
0
Order By: Relevance
“…Detailed investigation of their molecular mode of action revealed that they are able to inhibit at least three enzymes: FPP synthase [137], 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase [159] and glutamine synthetase (GS) [160]. Docking performed using Insight 2000 program package showed that two herbicidally active compounds 116 and 124 readily fit the active sites of all three enzymes with comparable potency [154].…”
Section: Glutamine Synthetasementioning
confidence: 99%
“…Detailed investigation of their molecular mode of action revealed that they are able to inhibit at least three enzymes: FPP synthase [137], 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase [159] and glutamine synthetase (GS) [160]. Docking performed using Insight 2000 program package showed that two herbicidally active compounds 116 and 124 readily fit the active sites of all three enzymes with comparable potency [154].…”
Section: Glutamine Synthetasementioning
confidence: 99%
“…The only exception is to now the zwitterion of the parent acid 1-a (Scheme 1), which despite almost equal populations of the E and Z in solution crystallizes as the E isomer [11]. Herein we present the solid state and solution behavior of three new members of this family, namely, (3,5-dibromo-6-methylpyridin-2-yl)aminomethane-1,1-diphosphonic acid (2), (3-chloro-5-trifluoromethylpyridin-2-yl)aminomethane-1,1-diphosphonic acid (3) and (pyrimidin-2-yl)aminomethane-1,1-diphosphonic acid (4). The latter compound may be considered as the derivative of 1-a, in which atom C-3 is replaced by a nitrogen atom (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Although first developed at the end-seventies of the twentieth century [1], they are examined intensely to date. At first, they have been probed as potential inhibitors of 3-deoxy-D-arabino-heptulosonate-7-phosphate (DAHP) synthase [2] and glutamine synthetase [3,4]. The most recent studies have indicated that compounds of this class rank among very potent inhibitors of the FPP synthase, an enzyme of the mevalonate pathway now considered as a major target of nitrogen-containing bisphosphonates in human, parasitic protozoa, and plant cells [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to ascertain that 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase could represent the main target of compound 15 in vivo, studies of the effect of sublethal concentrations of this compound on the pool of free amino acids in cultured Nicotiana plumaginifolia cells were undertaken [20]. The results obtained with compound 15 showed a strikingly different pattern than that found for glyphosate.…”
mentioning
confidence: 99%
“…Unlike phosphinithricin, which inactivates glutamine synthetase irreversibly, compound 15 binds reversibly to the enzyme, and this could account in part for the noteworthy effectiveness of the compound in vivo, as compared to that of the former. Thus, inhibition of both aromatic amino acids and glutamine biosynthesis might be an unusual mode of action of herbicidal compound 15 [20].…”
mentioning
confidence: 99%